2004
DOI: 10.1158/0008-5472.can-03-2833
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cables, a Cyclin-Dependent Kinase Regulatory Protein, Is Associated with the Development of Endometrial Hyperplasia and Endometrial Cancer

Abstract: Endometrial cancer is the most common gynecological cancer in Western industrialized countries. Cables, a cyclin-dependent kinase binding protein, plays a role in proliferation and/or differentiation. Cables mutant mice are viable, but develop endometrial hyperplasia and carcinoma in situ at a young age. Exposure to chronic low levels of estrogen results in development of endometrial cancer, similar to that observed in the postmenopausal female. In vitro and in vivo studies demonstrate that levels of Cables mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 18 publications
2
71
1
Order By: Relevance
“…22 Cables is lost in a variety of cancers, including head and neck, lung, endometrial, ovarian, and colon cancers. 13,16,23,24 Our results show that Cables expression is frequently absent in malignant colonic epithelium. Cables expression by immunostaining was decreased or absent in 65% (105 of 160) of primary CRCs.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…22 Cables is lost in a variety of cancers, including head and neck, lung, endometrial, ovarian, and colon cancers. 13,16,23,24 Our results show that Cables expression is frequently absent in malignant colonic epithelium. Cables expression by immunostaining was decreased or absent in 65% (105 of 160) of primary CRCs.…”
Section: Discussionmentioning
confidence: 56%
“…13 Previous studies found that Cables gene deletion leads to abnormal endometrial epithelial growth in mice. 16 Likewise, in response to a carcinogen (1,2-dimethylhydrazine), Cables Ϫ/Ϫ mice have an increased incidence of colorectal tumors and reduced survival rates compared with Cables ϩ/ϩ mice. 17 Furthermore, primary mouse embryonic fibroblasts from the Cables Ϫ/Ϫ mice show an increased rate of cell proliferation, delayed onset of senescence, and increased growth in low serum concentration.…”
mentioning
confidence: 99%
“…It is located on chromosome 18q11-12, a site frequently deleted in many primary human cancers. Loss of Cables expression was found in greater than 50% of endometrial, 4 colon, 2 lung 5 and ovarian 6 cancers and this correlated with loss of heterozygosity (LOH) on chromosome 18q11-12 in many of these tissues. 2 Stably transfected cultured cell lines that overexpress Cables demonstrated a reduction in cell proliferation compared to cells transfected with a vector control.…”
Section: Introductionmentioning
confidence: 99%
“…Cables -/-mice display endometrial hyperplasia and carcinoma-in-situ at a young age. 4 The Cables -/-mice are also much more prone to the development of colonic tumors following carcinogen treatment. 8 To further investigate Cables as a regulator of the cell cycle and cell proliferation, we compared proliferation, senescence and survival in primary MEFs derived from Cables +/+ and Cables -/-animals.…”
Section: Introductionmentioning
confidence: 99%
“…31 Previous studies showed that Cables1-null mutant mice displayed increased cellular proliferation (eg, endometrial hyperplasia, colon cancer, and oocyte development). [27][28][29] In contrast to Cables1 loss-of-function mutation, overexpression of Cables1 in a colon cancer cell line showed tumor suppressor activity, including inhibition of colony formation and cell growth. 32 However, there have been no reports that aberrant expression of Cable1 is involved in neural defects in vivo.…”
Section: Truncated Cables1 Causes Acc S Mizuno Et Almentioning
confidence: 95%